A novel analysis framework for the organic Rankine cycle waste heat recovery system: From the viewpoint of turbine design. (April 2022) - Li, Wenyu; Ling, Xiang
Abstract: The turbine is crucial equipment in the ORC system, not only has a significant influence on system efficiency but also dominates the equipment investment costs. In this paper, a novel design framework for the radial inflow turbine is proposed, aiming to promote the standardization or serialization design of the ORC turbine, and the innovativeness of combining it into the system analysis is illustrated. The reliability of the design framework is examined by comparing with CFD simulation, nearly all of the deviations within ±5%. Better prediction accuracy can be achieved when R is close to 0.6, and the suitable value of α 4 is 65° to realize a better turbine performance. Some other results reveal that the Ẇ out has a positive proportional to r 4 and Ma 4, but η ts is not sensitive to them. Besides from the viewpoint of thermodynamics, the η ts of the turbine is hardly affected by the type of working fluid. For the case study, the turbine with R236ea has achieved the best matching degree with the heat source, which improves near 10% of the total output power for the MGT-ORC system. This paper gives new ideas for ORC turbine design and system analysis which contributes to promoting its application.